1997
DOI: 10.1016/s1097-2765(00)80004-0
|View full text |Cite
|
Sign up to set email alerts
|

An Orphan Receptor Tyrosine Kinase Family Whose Members Serve as Nonintegrin Collagen Receptors

Abstract: Mammalian cells constantly monitor and respond to a myriad of extracellular signals, often by using cell surface receptors. Two important classes of cell surface receptors include the receptor tyrosine kinases, which recognize peptide growth factors such as insulin, and the integrins, which most often mediate binding to components of the extracellular matrix. We report that the collagens serve as ligands for the previously orphan family of discoidin domain-containing receptor-like tyrosine kinases. The unexpec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
474
0
5

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(493 citation statements)
references
References 39 publications
14
474
0
5
Order By: Relevance
“…3C), and lasted for at least 24 hours, consistent with earlier studies [Shrivastava et al, 1997;Vogel et al, 1997]. Levels of tyrosine phosphorylated DDR1 CTFs, and ectodomain release, both increased in a concentration-dependent fashion following prolonged exposure to collagen type I, although the DDR1 fragments were not detected until hours after phosphorylation of full-length DDR1 was first apparent (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3C), and lasted for at least 24 hours, consistent with earlier studies [Shrivastava et al, 1997;Vogel et al, 1997]. Levels of tyrosine phosphorylated DDR1 CTFs, and ectodomain release, both increased in a concentration-dependent fashion following prolonged exposure to collagen type I, although the DDR1 fragments were not detected until hours after phosphorylation of full-length DDR1 was first apparent (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…In 1997, two groups reported that DDR1 and DDR2 are collagen receptors [Shrivastava et al, 1997;Vogel et al, 1997]. The addition of collagen to the medium of cells expressing either DDR1 or DDR2 resulted in tyrosine phosphorylation of these receptors with a timecourse that was delayed in onset and lasted for up to 18 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Such a mechanism is illustrated by the type I collageninduced activation of tyrosine kinases of the discoidin domain receptor which ultimately trigger the synthesis of MMP-1. However, the MMP-1 -mediated cleavage of collagen abolishes the receptor activation, creating a specific negative-feedback regulatory loop [67,68]. In the presence of broad-spectrum MMPIs, the impaired collagen degradation might prevent this negative regulation, resulting in an uncontrolled stimulation of MMP-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…4). MLBR 2 extends from helical position 682-830, and includes sites important for collagen self-assembly [Prockop and Fertala, 1998], for cleavage by matrix metalloproteinases (MMPs) 1, 2, and 13 [Lauer-Fields et al, 2000], as well as for binding by α1β1/α2β1 integrins [Xu et al, 2000], fibronectin [Dzamba et al, 1993;Kleinman and McGoodwin, 1976;Kleinman et al, 1978], cartilage oligomeric matrix protein (COMP) [Rosenberg et al, 1998], phosphophoryn [Dahl et al, 1998], and possibly the discoidin domain (DDR2) receptor [Schlessinger, 1997;Shrivastava et al, 1997;Vogel et al, 1997]. MLBR 3 extends from helical residue 920 to the end of the helical region.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%